2020
DOI: 10.5114/wiitm.2020.93463
|View full text |Cite
|
Sign up to set email alerts
|

The risk of sarcopenia 24 months after bariatric surgery - assessment by dual energy X-ray absorptiometry (DEXA): a prospective study.

Abstract: Introduction: Bariatric procedures lead to changes in body composition. Desired fat loss may be accompanied by decrease of muscle mass, thus raising the risk of sarcopenia. Aim: To detect the risk of sarcopenia in patients 24 months after different bariatric/metabolic (B/M) procedures by DEXA. Material and methods: Consecutive patients scheduled for a B/M procedure underwent DEXA scan and anthropometric assessment before and 24 months after surgery in a prospective manner. Obtained data were tested for signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(33 reference statements)
0
19
0
1
Order By: Relevance
“…The retention and/or gain of fat-free mass, which largely reflects skeletal muscle, following bariatric surgery is important to maintain metabolism, support weight maintenance, and prevent complications such as sarcopenia [ 47 49 ]. Despite a loss of fat-free mass being expected following bariatric surgery [ 49 ] and observed early in the LSG cohort, the ESG cohort managed to increase fat-free mass at 6-months. Although the increase of approximately 0.3 kg was statistically significant, it is not clinically significant, so should be interpreted as maintaining fat-free mass only.…”
Section: Discussionmentioning
confidence: 99%
“…The retention and/or gain of fat-free mass, which largely reflects skeletal muscle, following bariatric surgery is important to maintain metabolism, support weight maintenance, and prevent complications such as sarcopenia [ 47 49 ]. Despite a loss of fat-free mass being expected following bariatric surgery [ 49 ] and observed early in the LSG cohort, the ESG cohort managed to increase fat-free mass at 6-months. Although the increase of approximately 0.3 kg was statistically significant, it is not clinically significant, so should be interpreted as maintaining fat-free mass only.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that although bariatric surgery is effective at lowering the BMI, this procedure may also induce sarcopenia post-operatively. 22,23 Thus, with the known risks of sarcopenia shown within our study, it may be inadvisable to recommend bariatric surgery to improve BMI prior to undergoing complex revision thoracolumbar spine surgery.…”
Section: Discussionmentioning
confidence: 79%
“…The necessity of controlling diabetes treatment and dietary recommendations is widely known. However, it should not be forgotten that the consequences of the bariatric surgery bring the need to monitor a wide range of factors, such as the psychological aspect, the level of physical activity [ 10 ], and even the risk assessment of a planned pregnancy [ 11 ].…”
Section: Resultsmentioning
confidence: 99%